A robust neural familiar face recognition response in a dynamic (periodic) stream of unfamiliar faces. (November 2020) - Yan, Xiaoqian; Rossion, Bruno
Abstract: We present an objective and sensitive approach to measure human familiar face recognition (FFR) across variable facial identities. Twenty-six participants viewed sequences of natural images of different unfamiliar faces presented at a fixed rate of 6 Hz (i.e., 6 faces by second), with variable natural images of different famous face identities appearing periodically every 7th image (i.e., .86 Hz). Participants were unaware of the goal of the study and performed an orthogonal task. Following only seven minutes of visual stimulation, the FFR response was objectively identified in the EEG spectrum at .86 Hz and its harmonics (1.71 Hz, etc.) over bilateral occipito-temporal regions, being significant in every individual participant. When the exact same images appeared upside-down, the FFR response amplitude reduced by more than 80%, and was uncorrelated across individuals to the upright face response. The FFR for upright faces emerges between 160 and 200 msec following the famous face onset over bilateral occipito-temporal region and lasts until about 560 msec. The stimulation paradigm offers an unprecedented way to characterize rapid and automatic human face familiarity recognition across individuals, during development and clinical conditions, also providing original information about the time-course and neural basis of human FFR in temporally constrained stimulation conditions with natural images.